Factors Associated with Length of Stay in Psychiatric Inpatient Services in London, UK - Newman, Loveday (Psychiatr Q, 2017)
The purpose of this research was to identify factors associated with lengthy stays in psychiatric hospital in a UK mental health trust. A multiple regression using a multiple imputation method to deal with missing data was performed on inpatient admissions data over a four-year period for 7653 individuals. Factors associated with a longer length of stay included gender (being male), ethnicity (being Asian/Asian British, Black/Black British, or having a mixed background compared to being White/White British), accommodation status (being homeless, or in accommodation with support), primary diagnostic group of psychosis (F20–29), and number of care coordinators. Marital status was not found to be associated with length of stay in this sample. Length of stay is likely to be multifactorially determined, and more similar studies examining factors associated with length of hospital stay are needed to understand the operation of psychiatric services.